EVALUASI KINERJA KEUANGAN DENGAN METODE KOMPARATIF DAN TREND PADA PT. ANGKASA PURA I (PERSERO) PERIODE 2012-2016 - Pangihutan, Fredy Linggom; Simamora, Saur Costanius (JURNAL BISNIS & AKUNTANSI UNSURYA, 2019)
This study aims to evaluate the progress and know the level of health to assess the financial performance of PT.AP I period 2012-2016.The type of this research is descriptive with quantitative approach where the quantitative data type in the form of company financial statements and secondary data sources with data collection techniques documentation.The results of the analysis in this study showed that the development of financial performance of the company has a positive upward trend with favorable trends during the period 2012-2016 where the year 2016 a rising trend proportional because the increase in operating revenues exceeded the increase in operating expenses that led to the profit of the current year to be maximal from year , and health rating based on Ministerial Decree of SOE No: KEP-100 / MBU / 2002 seen from the financial aspect looks less good because the company get less healthy predicate with BBB category in 2012 (57,5), 2013 (51 ), 2014 (58), 2015 (62), while the company gets a healthy predicate with category A in the year 2016 (66), then the average score score during 2012-2016 amounted to 58.9 which get less healthy predicate with category BBB, then the result of data analysis can be obtained that financial performance PT.AP I year 2012-2016 seen from eight financial ratios (Current Ratio, Cash Ratio, TMS for TA, ROE, ROI, PP, CP, TATO) have not been different for the last 5 years.